1995
DOI: 10.1128/aem.61.7.2589-2595.1995
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium chrysogenum Takes up the Penicillin G Precursor Phenylacetic Acid by Passive Diffusion

Abstract: Penicillium chrysogenum utilizes phenylacetic acid as a side chain precursor in penicillin G biosynthesis. During industrial production of penicillin G, phenylacetic acid is fed in small amounts to the medium to avoid toxic side effects. Phenylacetic acid is taken up from the medium and intracellularly coupled to 6-aminopenicillanic acid. To enter the fungal cell, phenylacetic acid has to pass the plasma membrane. The process via which phenylacetic acid crosses the plasma membrane was studied in mycelia and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 31 publications
(31 reference statements)
6
24
2
Order By: Relevance
“…2B). These data indicate that uptake of PA occurs through simple diffusion, in accordance with earlier conclusions (Hillenga et al, 1995). However, at low external PA concentrations in the range from 2.3-100 M, the kinetics of accumulation in the two strains differed, as in the Wisconsin strain accumulation of total PA and PA-derived carbon showed saturation kinetics with apparent K m of 15 M and V max of 109 pmol/mg dry weight per min ( Fig.…”
Section: Uptake Of Pa In Penicillium Chrysogenumsupporting
confidence: 91%
See 3 more Smart Citations
“…2B). These data indicate that uptake of PA occurs through simple diffusion, in accordance with earlier conclusions (Hillenga et al, 1995). However, at low external PA concentrations in the range from 2.3-100 M, the kinetics of accumulation in the two strains differed, as in the Wisconsin strain accumulation of total PA and PA-derived carbon showed saturation kinetics with apparent K m of 15 M and V max of 109 pmol/mg dry weight per min ( Fig.…”
Section: Uptake Of Pa In Penicillium Chrysogenumsupporting
confidence: 91%
“…In contrast, early results suggested that PA and other weak acids penetrate the plasma membrane of P. chrysogenum by simple diffusion of the undissociated acids (Hunter and Segel, 1973), and recently Hillenga et al (1995) concluded that uptake of PA in P. chrysogenum Wisconsin 54-1255 and Panlabs P2 occurs through simple diffusion of the undissociated PA across the plasma membrane. One reason for the conflicting conclusions on kinetics of PA uptake in P. chrysogenum may be the different concentration ranges employed; low external concentrations of PA (1.4-100 M) were used by Fernández-Cañón et al (1989a,b), whereas higher PA concentra-tions (60-30,000 M) were applied by Hillenga et al (1995).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…With respect to nitrate it is assumed that uptake is similar to nitrate uptake in Neurospora crassa; that is, active transport through proton symport with a stoichiometry of 2H + per NO 3 − anion transported across the membrane (Blatt et al, 1997). Transport of phenylacetic acid in P. chrysogenum has been reported to occur through passive diffusion (Hillenga et al, 1995).…”
Section: Solute Transport Across the Plasmalemmamentioning
confidence: 99%